Uma história social da Assembléia de Deus : a conversão religiosa como forma de ressocializar pessoas oriundas do mundo da criminalidade. - Andrade, Moisés Germano de (2010)
This research aims to analyze the life stories of people who took the crime world through a cultural and spiritual relationship with the Church Assembly of God, in the neighborhood of Knight, Jaboatao dos Guararapes, in the last ten years. We are here analyzing speech and the method using the Assembly of God in the process of resocialization of people from the world of crime, concatenating with the testimony produced by resocializing studying conditions of sense these discourses between individuals who converted after a life of crime in the world . We are interested in, particularly in this analysis, consider the brands of memory and memories of these individuals, which tell about their conversion and transformations in their lives.